A Rosetta Stone for eastern Pacific Caecidae (Gastropoda: Caenogastropoda) - Raines, Bret K. (Zootaxa, 2020)
Nearly one hundred names have been proposed for Caecidae within the eastern Pacific. For the first time a comprehensive review of the extant members of Caecidae has been completed for this region. During this twelve year long deciphering effort, tens of thousands of specimens from Alaska to Chile were examined. All known type material was studied and whenever possible has been illustrated herein. Whenever possible the descriptions include details of each growth stage from the protoconch through to the final adult stage. Then, the growth stages have been reconstructed to show what the caecid might have looked like, if it had not discarded its previous stages. In doing so, a better understanding of the growth morphology is provided for each species. In addition, this effort shows that not only the apertures of late subadult stages can appear different from their adult stage, but there can also be multiple differences in the varices. The resulting product is a taxonomic resource for Caecidae identification and growth morphology. Forty-three species are treated herein. Neotypes have been designated for Caecum glabriforme, C. semilaeve and C. subaustrale, and a lectotype has been designated for C. mirificum. Five species are described as new to science, plus one replacement name: Caecum lightfootanum sp. nov., C. draperi sp. nov., C. shaskyi sp. nov., C. galapagoense sp. nov. and C. spiculum sp. nov. and C. adamsi nom. nov.